Primary Peritoneal Angiosarcoma Metastatic to Liver and Bone without History of Radiation Therapy - Way Chiang; Zofia Tynski (Hindawi Limited, 2018)
Angiosarcoma is a rare vascular soft tissue tumor of endothelial origin most commonly seen in the elderly as a primary cutaneous head and neck malignancy. Furthermore, a peritoneal angiosarcoma is an exceedingly rare entity. This is the second case of primary peritoneal angiosarcoma reported in literature that is not associated with prior radiotherapy. Herein, we describe a case of primary peritoneal angiosarcoma metastatic to both the liver and bone in a male patient with metachronous renal cell carcinoma and parathyroid adenoma.